Modular Design and Thermal Modeling Techniques for the Power Distribution Module (PDM) of a Micro Satellite - Anwar Ali; Haider Ali; Jijun Tong; Muhammad Rizwan Mughal; Saeed Ur Rehman (IEEE Access, 2020)
The power distribution module (PDM) is one of the vital modules onboard small satellites and its design governs the performance of all the subsystems including communication, attitude determination & control, navigation, payload, etc. The paper presents the design of the PDM developed for the Pakistan National Student Satellite-1 (PNSS-1). The main focus of the design is modularity, redundancy, design reuse and miniaturization using commercial off the shelf (COTS) components. PDM is the sub-module of electric power system (EPS) which converts the power distribution bus (PDB) voltage level (unregulated 28V) into the secondary voltage levels and to distribute these voltages to loads according to their requirements. In order to improve reliability and to overcome various failures, redundancy is provided at all levels. No single component failure in PDM disables or degrades its intended functions that may lead to mission failure. Latch-up protection circuit is designed for the CMOS processor and at the end a thermal model is presented for the PDM unit.